2021
DOI: 10.1002/pan3.10231
|View full text |Cite
|
Sign up to set email alerts
|

Relational values help explain green infrastructure preferences: The case of managing crane habitat in Hokkaido, Japan

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Relational values are about, or based on, meaning‐saturated relationships (Chan et al, 2018) and represent preferences, principles and virtues associated with interpersonal relationships with ‘nature’ and with others, that make a good life (Chan et al, 2016). In places such as coasts, which are ‘always in the process of becoming through heterogeneous interrelations’ (Leyshon, 2018: 155), focusing on relationships between people and place is particularly important, and recent research has shown that relational values are useful in decision‐making around wetland management in particular (Bataille et al, 2021; Kim et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Relational values are about, or based on, meaning‐saturated relationships (Chan et al, 2018) and represent preferences, principles and virtues associated with interpersonal relationships with ‘nature’ and with others, that make a good life (Chan et al, 2016). In places such as coasts, which are ‘always in the process of becoming through heterogeneous interrelations’ (Leyshon, 2018: 155), focusing on relationships between people and place is particularly important, and recent research has shown that relational values are useful in decision‐making around wetland management in particular (Bataille et al, 2021; Kim et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…These studies developed original survey items to measure relational values (e.g. Klain et al, 2017; Saito et al, 2021), compared values held by urban and rural community members (Bashan et al, 2021), mapped the values of various ecosystem services across landscapes (Garcia‐Diez et al, 2020), compared benefits of forest management approaches among instrumental and relational values (Himes et al, 2020), explored the mechanics of how people form relational values in specific ecosystems (Flood et al, 2021), and used the relational values concept to re‐analyse results from a survey designed to elicit economic values associated with bird habitat (Kim et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…in items that emphasize participants' relationships to various natural contexts). Kim et al (2021) used relational values to re‐assess results from a choice experiment that were not fully explained by neoclassical economic theory. Himes et al (2020) assessed trade‐offs among various forest ecosystem services, and they used relational values to capture the values of those ES on different societal scales.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This establishes the proportions of people with specific preferences. Such information is also useful when considering consensus building over green infrastructures [43].…”
mentioning
confidence: 99%